Forms of Boron and its Distribution in Saline-Alkali Soils - D.S. Chahal, Sanjay Arora (Journal of the Indian Society of Soil Science, 2015)
Seven forms of boron (B) using different extractants were determined in salt affected benchmark soils of Punjab. The soil pH varied from 8.60 to 10.24, EC from 0.13 to 4.8 dS m-1, CaCO3 content from 0.30 to 26.8 g kg-1 and organic C from 1.1 to 5.5 g kg-1. The content of water soluble (WS-B), hot water soluble (HWS-B), hot 0.01 M CaCl2 soluble (HCC-B), acid soluble (HCl-B), leachable or mannitol extractable (Mann-B) and AB-DTPA extractable B in salt affected soils of Punjab, ranged from 0.16 to 2.48, 0.30 to 4.80, 0.20 to 3.20, 0.32 to 3.40, 0.28 to 4.20 and 0.14 to 0.84 mg kg-1 soil, respectively. Forms of B were positively and significantly related with soil pH and EC. Total B ranged from 11.26 to 30.25 mg kg-1 and was non-significantly correlated with other forms. The HWS-B was significantly correlated with HCC-B (r = 0.969**). Regression equation showed 97 to 99% variations in WS-B, HWS-B, HCC-B, HCl-B, Mann-B, and AB-DTPA-B while only 77% in total B content governed by various soil properties.